In Vitro and Computational Analyses of Blood Flow at Aortoiliac Bifurcation for Patients with Atherosclerotic Plaque Treated with Endovascular Procedures - Chong, Albert (Curtin University, 2020)
This research has developed an appropriate approach allowing for more accurate assessment of haemodynamic changes following implantation of endovascular stent graft to treat patients with occlusive aortoiliac disease. Two different endovascular techniques involving the use of different types of stent grafts were analysed and compared with regard to haemodynamics associated with these techniques. Results improved understanding of the flow characteristics of these endovascular techniques.